IMPREGNASI KAYU KELAPA SAWIT POSISI INTI MENGGUNAKAN ASAP DESTILAT CANGKANG BUAH KELAPA SAWIT KOMBINASI ASAM AKRILAT - Denny Akbar Tanjung (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2018)
This research aims to improve the quality or durability of mechanical properties with the process of impregnation destilat smoke combination of acrylic acid into the trunks of KKS part edge. The stages are done in this research are: manufacture of destilat smoke 2000C temperature of the outer shell of the fruit of the oil palm, palm oil wood cutting position of the edge of 2, 4, 6, 8 meters from the ground up, with the destilat smoke KKS Impregnation combinations of acrylic acid, testing mechanical properties, Photo SEM and durability. Of research results obtained the maximum density adalah0,75 gr/cm3, Modulus of a broken (MOR) maximum of 283,7 kg/cm2, Elastic Modulus (MOE) 53.289,4 kg/cm2, the shear stress parallel 52,77 kg/cm2. To test the durability of the fungus cannot live on the KKS has been impregnated. Keywords: Impregnation of oil palm wood, destilat smoke, acrylic acid, Modulus Elastic, Broken Modulus, Shear Stress Parallel Fibers.